Design of MySuper default funds: influences and outcomes. (18th May 2015) - Butt, Adam; Donald, M. Scott; Foster, F. Douglas; Thorp, Susan; Warren, Geoffrey J.
Abstract: We interview Australian fund executives about how their organisations responded to MySuper, a regulatory framework for default retirement savings funds that providers were required to have in place by the beginning of 2014. We provide an account of the influences on MySuper product design. Our analysis generates insight into how fund providers balanced their perceptions of the needs of default fund members against business considerations. Differences in member bases and organisational circumstances across funds are found to lead to considerable variation in default fund design.